Reimagining Ethical Leverage in Technology for Peaceful Synodality: A Bioethics of Synodality with Technology - Mwakio, Pascal Mwambi (Religions, 2024)
This paper seeks to reimagine ethical leverage in technology for peaceful synodality (the term peaceful synodality is coined to mean a synodality that welcomes participation and inclusion of people from different backgrounds and views without compromising the truth and respecting their dignity and journeying together) through the lens of the bioethics of synodality with technology. The concept of this paper is that technology can be leveraged ethically to promote peaceful synodality in the Catholic Church and that such an approach to technology is rooted in reimagining a bioethics of synodality that emphasize the need for journeying hand in hand with the speed at which technological advancement moves in order to enhance ethical decision-making processes. Ethics has moved at a different pace than technology, especially in matters involving human life. Ethics has been viewed as problematic in technology, especially where science wants to be neutral, but rethinking ethics as a companion of emerging technologies will be helpful in directing the ethical uptake of technology. To argue this thesis, the paper will employ a review of relevant literature while presenting the theological and ethical perspectives of synodality. By and large, an interdisciplinary approach will be employed where various disciplines play a key role. Such methodology advances the theme of reimagining Catholic ethics by offering a fresh perspective on the ethical implications of technology in the context of synodality. By emphasizing the importance of journeying together through enhanced ethical guidelines for proper decision-making and by exploring how technology can respect human rights and dignity among other values, this paper contributes to a broader conversation about how Catholic ethics can be reimagined in light of technological developments. Ultimately, this paper argues that a bioethics of synodality with technology can offer a vision for technology that is grounded in Catholic social teaching that promotes universally accepted human dignity and the common good. A cross-cutting method will also be used, given that ethics has basically constant principles, yet technology keeps on changing. Reimagining ethics means studying the advancement brought about by biotechnology and seeing to what degree human beings are affected in their basic rights and the risks versus the benefits brought about by the same. The assumption is that decisions made regarding the ethics of various technologies will be at par with the rate at which new technologies emerge and are employed. What is of vital importance is that ethics can have the power to journey together with technology, not as an adversary but in synodality. Reimagining ethics means being ever alert in the developing technologies that serve humanity so that in consultation with various experts, the best practices can be embraced within the ethical guidelines for the common good. The outcome of this research is that reimagining Catholic ethics involves listening to the needs of humanity and how technology is bringing solutions to them. Participating in bioethical debates, training on bioethics and listening to experts in various fields will enable a critical, analytical and pneumatological discernment of how ethical decisions on frontier technologies can benefit non-humans and humans.